Synchronized Work System Through Digital Media as a Modern Workplace Solution - Marteen Joshe Octavian; Trisha Narendragarini; J.A Wempi (Eduvest - Journal of Universal Studies, 2025)
Remote and hybrid work models have become essential in today’s business environment, especially after the COVID-19 pandemic, as many organizations continue to embrace them as sustainable long-term strategies. In an increasingly dynamic market, these systems help companies remain competitive by fostering effective virtual collaboration. This study aims to understand the implementation of synchronized work systems through digital media and how these tools serve as modern workplace solutions in Indonesia. Guided by the theory of Computer-Mediated Communication, the research analyzes the role of digital platforms in enhancing communication efficiency and productivity. Using a collective case study and literature review method, the study explores the work policies of three Indonesian companies in the technology, education, and health sectors that have adopted hybrid and Work From Anywhere (WFA) models. The findings reveal that tools such as Slack, Trello, Google Workspace, and WhatsApp play a significant role in supporting synchronized work, though their success depends on clear communication strategies and a balance between formal and informal interactions. However, challenges such as unclear work boundaries, burnout risks, and coordination issues persist and require structured management to maintain collaboration and sustainability. The study concludes that to implement flexible work systems effectively, companies must select appropriate digital tools, provide ongoing communication training, and maintain equilibrium between virtual teamwork and face-to-face engagement to ensure productivity and employee well-being.